Crimea under the Rule of the Ottomans and the Dispute over Conclusion of the Agreement: Based on New Documents (1) - Halil İnalcık (Золотоордынское обозрение)
he article examines the period of transition of the territory of Crimea under the protectorate of the Ottoman Empire. Recently in the archives of the Topkapi Palace Museum, new documents have been discovered on the history of the Golden Horde containing the letters of the Crimean khans and beys. On the basis of these new historical sources, the author clarifies the contentious issues related to the agreement between Sultan Mehmed the Conqueror and Mengli I Giray and reveals the reasons that influenced the way the Crimea became subservient to the Ottoman Empire.